KEANEKARAGAMAN JENIS BAMBU DI HUTAN KOTA KELURAHAN BUNUT KABUPATEN SANGGAU - syah, Ridwan; Husni, Harnani; Wulandari, Reine Suci (Universitas Tanjungpura, 2015)
Based on the identification result of research conducted in the area of ​​Forest City Sanggau found 3 types, namely Bamboo Buluh (Schizostachyum brahycladum Kurz, Bamboo Munti (Schizostachyum sp), and Betung Bamboo (Dendrocalamus asper (Schult) Becker ex. Heyne). Based on the analysis of identification observation of the entire plot there is a type of bamboo that has the highest INP. The dominant type of bamboo is a type of bamboo buluh with INP = 122.616%, dominance index value of 0.526 indicates that the pattern of dominance is spreading not concentrated on one type only; Diversity Index Type (H') that is equal to 0.31654 classified into low because the value of H' <1; the value of Wealth Index Type (d) in all kinds of bamboo that is equal to 2.57966 allegedly a growing factor that does not support to grow and thrive well for individuals of each species; Evenness index type (e) of 0.66344 indicates that the level of evenness of bamboo in Forest City area Sanggau uneven; Morisita index (Id) of 33.7058 whole bamboo species showed a tendency deployment groups. And when viewed from the calculation of Truth Chi-square test results obtained by 2186.564 This indicates that the Chi-square test was significantly different meaning deployment groups. Keywords: Diversity, the forest city, bamboo